Malaysian batik painting from 1950 to 2010: a study on style / Anis Ediana Mohd Fauzi...[et.al] - Mohd Fauzi, Anis Ediana; Ghazali, Noor Hafiza (2016)
Throughout these few past decades batik painting in Malaysia has gone through a lot of growth as well as changes in techniques, idea and ways of producing batik painting artworks. Batik painting has become one of the additional media by some artists in Malaysia. In this thesis the researcher attempt to study and analyze on the styles of the batik painting in Malaysia from 1950s to the 2010s. The objectives and aims of this research are to study the development of styles in Malaysian batik painting; to study the history and development of Batik Painting in Malaysia; to analyze the style of Malaysian Batik Painting in from 1950s until 2000s; to come up with the classification of styles of Malaysian batik painting. The research methodology use is qualitative. Thirteen batik painting artworks were selected by seven batik painting artist. The researcher used Feldman method of criticism that comprises four strategies of criticism, which are description, analysis, interpretation and evaluation to criticize and appreciate the artworks. The researcher analyzed the data based on the theory of style used by art historian, Paul Zucker in order to determine the styles used. The findings of the research showed that most of Malaysian batik painting artists have been strongly influenced by the National Cultural Congress as it can be seen through the production of batik painting in this time period. Meanwhile, most of the ideas and images are based on the spiritual movement that emphasizes on religious as well as cultural factors prompted by the congress. Education is also an important factor in the development of style in Malaysian batik painting, where all selected artists had received formal art education from different countries and school of arts, locally or internationally.